2018
DOI: 10.1007/s10067-018-4136-9
|View full text |Cite
|
Sign up to set email alerts
|

The first case of bacillus Calmette-Guérin-induced small-vessel central nervous system vasculitis

Abstract: To present an unrecognized vascular complication of bacillus Calmette-Guérin (BCG) therapy administered for superficial bladder carcinoma. We also review the potential mimickers for primary angiitis of the central nervous system (PACNS) as well as complications of intravesical BCG therapy. An 89-year-old Caucasian man with a history of relapsing high-grade bladder carcinoma treated with intravesical BCG presented with recurring episodes of right upper limb paresthesia with clumsiness and dysarthria. Magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…141 Cases of endophthalmitis, uveitis, vitiligo, meningitis, aortitis, or mycotic aneurysms have been reported as well as central nervous system vasculitis. [142][143][144] BCG administration has also been related to the pathogenesis of Takayasu arteritis or KD. 59,145 Recently, a study in Finland showed that discontinuing universal BCG vaccination did not changed the incidence rates of KD, however the mean age at diagnosis increased, suggesting that the pathogenesis of KD may be associated with immunological priming by BCG vaccination.…”
Section: Complications Of Bcg Immunizationmentioning
confidence: 99%
“…141 Cases of endophthalmitis, uveitis, vitiligo, meningitis, aortitis, or mycotic aneurysms have been reported as well as central nervous system vasculitis. [142][143][144] BCG administration has also been related to the pathogenesis of Takayasu arteritis or KD. 59,145 Recently, a study in Finland showed that discontinuing universal BCG vaccination did not changed the incidence rates of KD, however the mean age at diagnosis increased, suggesting that the pathogenesis of KD may be associated with immunological priming by BCG vaccination.…”
Section: Complications Of Bcg Immunizationmentioning
confidence: 99%
“…17 In addition, a case of BCG-induced small-vessel CNS vasculitis was also reported. 18 To our knowledge, the present report is the first to describe a case of BCGitis associated brain tuberculomas in an immunocompetent child. Possible factors, such as impaired Th1 immunity in early life, underlying immunodeficiency, or HIV can cause complications.…”
Section: Discussionmentioning
confidence: 61%
“…Up to 5% of the patients develop serious systemic side effects with inflammation up to life threatening sepsis (2) or immunologic reactions such as myasthenia gravis (3,4). Two recent publications presented cases of small-vessel central nervous system vasculitis caused by BCG, but in contrast to our case, these reports pointed toward an acute BCG infection as underlying cause and patients were treated by either tuberculostatic therapy only (5) or in combination with steroids (6). Based on the pronounced response to immunosuppressive treatment with cyclophosphamide, we conclude an autoimmune etiology due to previous BCG instillations.…”
Section: Case Reportmentioning
confidence: 58%